Addressing anti-black racism in an academic preterm birth initiative: perspectives from a mixed methods case study - Shira P. Rutman; Natasha Borgen; Solaire Spellen; Dante D. King; Martha J. Decker; Larry Rand; Alexis Cobbins; Claire D. Brindis (BMC, 2023)
Abstract Background Growing recognition of racism perpetuated within academic institutions has given rise to anti-racism efforts in these settings. In June 2020, the university-based California Preterm Birth Initiative (PTBi) committed to an Anti-Racism Action Plan outlining an approach to address anti-Blackness. This case study assessed perspectives on PTBi's anti-racism efforts to support continued growth toward racial equity within the initiative. Methods This mixed methods case study included an online survey with multiple choice and open-ended survey items (n = 27) and key informant interviews (n = 8) of leadership, faculty, staff, and trainees working within the initiative. Survey and interview questions focused on perspectives about individual and organizational anti-racism competencies, perceived areas of initiative success, and opportunities for improvement. Qualitative interview and survey data were coded and organized into common themes within assessment domains. Results Most survey respondents reported they felt competent in all the assessed anti-racism skills, including foundational knowledge and responding to workplace racism. They also felt confident in PTBi's commitment to address anti-Blackness. Fewer respondents were clear on strategic plans, resources allocated, and how the anti-racism agenda was being implemented. Suggestions from both data sources included further operationalizing and communicating commitments, integrating an anti-racism lens across all activities, ensuring accountability including staffing and funding consistent with anti-racist approaches, persistence in hiring Black faculty, providing professional development and support for Black staff, and addressing unintentional interpersonal harms to Black individuals. Conclusions This case study contributes key lessons which move beyond individual-level and theoretical approaches towards transparency and accountability in academic institutions aiming to address anti-Black racism. Even with PTBi's strong commitment and efforts towards racial equity, these case study findings illustrate that actions must have sustained support by the broader institution and include leadership commitment, capacity-building via ongoing coaching and training, broad incorporation of anti-racism practices and procedures, continuous learning, and ongoing accountability for both short- and longer-term sustainable impact.